Analysis Characters in the Novel The Story of Tanah Jawa Pocong Bare - Nova, Emalia; Supratno, Haris; Suhartono, Suhartono (CV. Inara, 2024)
Research purposes This is describe character in the story novel pocong land of Java bald . Study This use approach qualitative descriptive . Object and subject study study This is a story novel land pocong bald . Deep data study This is contained character​ in the story novel pocong land of Java bald . Source of research data This is a story novel pocong land of Java bare work Christian Banisrael which was released in 2019. Data collection techniques were carried out with method read object study in a way deep accompanied with understanding A contained character​ in the novel . Research data analysis techniques qualitative This nature inductive , i.e something analysis based on the data obtained first with classify the data that has been recorded in the data recording list above categories or existing classifications , secondly existing data​ classified analyzed more further and more in Again For made base interpret all the data and the third Then conclude results study. Research result analysis character in the story novel pocong land of Java bare is character vengeful , angry , kind heartless , drunkard , obedient , and shy . Analysis story novel characters pocong land of Java bare this is also based on from the values contained inside it that is mark education , morals, and history.